Variations in soil carbon, nitrogen, and phosphorus concentrations and stoichiometry with stand age in Acacia hybrid plantations in Southern Vietnam - MAIHAI CHAU; NGUYENVAN QUY; XIAONIU XU; BUIMANH HUNG; LE VAN CUONG; TRANTHI NGOAN; THANHMINH NGUYEN (Society for Indonesian Biodiversity, 2024)
Abstract. Chau M, Quy N, Xu X, Hung B, Cuong LV, Ngoan T, Nguyen T. 2024. Variations in soil carbon, nitrogen, and phosphorus concentrations and stoichiometry with stand age in Acacia hybrid plantations in Southern Vietnam. Biodiversitas 25: 565-573. Soil Carbon (C), Nitrogen (N), and Phosphorus (P) contents are the three most critical soil nutrient elements required for plant growth and development, and their ecological stoichiometric ratios are significant indicators for understanding soil nutrient balance and cycling. This study was conducted to probe variations in the soil organic C (SC), total N (SN), and total P (SP) contents and stoichiometry at five soil depths (0-20, 20-40, 40-60, 60-80, and 80-100 cm) in Acacia hybrid plantations of five different ages (2-, 4-, 6-, 8-, and 10-year-old plantations) in Langa-Dongnai Forestry Company, Southern Vietnam. The results showed that forest age and soil depth substantially impacted soil nutrient contents and their stoichiometric characteristics. The concentrations of SC, SN, and SP as well as C/N, C/P, and N/P ratios increased as the forest stand age increased. The contents of SC, SN, and SP reduced with soil depth, indicating an obvious soil “surface-aggregation” phenomenon. The nutrient restriction varied based on forest stand development, shifting from restricted nitrogen in the earlier growth periods of trees to restricted phosphorus in the later growth periods. The findings demonstrate that to resolve the issue of restricted availability of these nutrient indexes, additional nitrogen should be supplied during earlier growth periods and additional phosphorus during later growth periods. The results further emphasize the importance of understanding SC, SN, and SP interactions and nutritional limitations and provide relevant theoretical support for sustainable Acacia hybrid plantation management in the Southern region.